Utilization of the Kahoot Games Application for Understanding Economic Learning in High School Students - Grida Saktian Laksito; Rabiu Hamisu Kankarofi (Research Collaboration Community (RCC), 2023)
Learning Economics is one of the lessons that need to be well understood by students. With the existence of the economy, students will have a basis for starting and managing the economy and businesses that will be built. Still, there are problems with students of SMAN 1 Majalaya, where they lack enthusiasm and feel less active in learning economics lessons. There needs to be an improvement in learning methods so that their interest in and understanding of basic economics increases, one of which is by utilizing the Kahoot Games application. This study used a quantitative approach with the method of testing the oneway ANOVA hypothesis with a total of 42 respondents who were students of class XI IPS 3 at SMAN 1 Majalaya. The results of the study explain that the use of the learning activity application using the Kahoot Games application has increased students' understanding of the importance of the economy in the daily lives of students so that participants who are Majalaya 1 Public High School students will easily understand basic economics lessons and begin to manage their finances properly.